Engineering of small-molecule lipidic prodrugs as novel nanomedicines for enhanced drug delivery - Lingling Huang; Jianmiao Yang; Tiantian Wang; Jianqing Gao; Donghang Xu (Journal of Nanobiotechnology, 2022)
Abstract A widely established prodrug strategy can effectively optimize the unappealing properties of therapeutic agents in cancer treatment. Among them, lipidic prodrugs extremely uplift the physicochemical properties, site-specificity, and antitumor activities of therapeutic agents while reducing systemic toxicity. Although great perspectives have been summarized in the progress of prodrug-based nanoplatforms, no attention has been paid to emphasizing the rational design of small-molecule lipidic prodrugs (SLPs). With the aim of outlining the prospect of the SLPs approach, the review will first provide an overview of conjugation strategies that are amenable to SLPs fabrication. Then, the rational design of SLPs in response to the physiological barriers of chemotherapeutic agents is highlighted. Finally, their biomedical applications are also emphasized with special functions, followed by a brief introduction of the promising opportunities and potential challenges of SLPs-based drug delivery systems (DDSs) in clinical application. Graphical Abstract